Predicting Quality of life of Schizophrenia Patients - Insiyah, Insiyah; Rohimah, Yeni Tutu; Astuti, Sri Lestari Dwi; Lestari, Siti; Suyanto, Suyanto; Sulistyowati, Endang Caturini (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: Previous studies on sociodemographic characteristics connected to quality of life in schizophrenia discovered inconsistent results. This study aims to analyze predicting factors of quality of life (QoL) of schizophrenia patients.  Methods: A quantitative study included 153 respondents who were selected using random sampling at the State Psychiatric Hospital Surakarta. The research instruments were a questionnaire containing questions about demographics consisting of age, age at first experiencing schizophrenia, gender, education level, work status, marital status, frequency of treatment, duration of suffering from schizophrenia, insight, physical health problems and quality of life by using WHOQOL-BREF. The analyses used were Spearmen's rank (rho) and the Pearson Chi-Square    to analyze factors connected to QoL of schizophrenia patients and multiple logistic regression tests to analyze predictors of QoL of schizophrenia patients. This study was conducted in the State Psychiatric Hospital of Surakarta from September 2020 to March 2021.  Results: There were 4 characteristics of sociodemographic that have a positive significant relationship with the overall quality of life of schizophrenia patient, namely work status (p = 0.000), marital status with p = 0.000, gender (p=0.032), and adherence to take medicine with p=0.015 (p <0.05). marital status and work status that influence the quality of life (p=0.000 and p=0.001).  Marital status and work status influence the quality of life (p=0.000 and p=0.001), the largest OR value obtained is 25.499.  It means that married patients have a 25.499 times chance of having a better quality of life controlled by work status.  Conclusion: Marital status and work status are predictors of QoL of schizophrenia. In providing services to schizophrenic patients, health professional need to pay attention in assessing social demographics such as work status and marital status so that appropriate action can be taken with an approach to these aspects.